Effect of Vacuum Concentration on the Volatile Flavor Substances of Crab Flavor of Hydrolysate of River Crab - Huijing FU; Yan LI; Dexiong SHEN; Li DING; Zijian WU; Lizhen MA (Shipin gongye ke-ji, 2023)
In order to understand the effect of heating on the crab taste change of river crab enzymolysis liquid (RCEL), this experiment used high pressure extract of low value river crab (HPEC) as substrate, hydrolyzed with flavor protease to obtain RCEL, and concentrated RCEL in vacuum. Firstly, the concentrated solution (CES) and evaporated water (EW) of enzymatic hydrolysis products were collected, and different vacuum concentration temperatures (20, 30, 40, 50, 60, 70 ℃) and concentration volumes (3/4, 1/2, 1/4 of the original volume) were set. Secondly, different CES and EW samples were collected for electronic nose PCA analysis. Headspace-solid phase microextraction and gas chromatography-mass spectrometry (HS-SPME-GC-MS) were used to analyze the changes of volatile flavor substances in HPEC, RCEL and 50CES and 50EW samples at 50 ℃ vacuum concentration temperature. The results of electronic nose analysis showed that the distance between CES and RCEL would obviously increase no matter how the temperature and volume changed, as long as the enzymatic hydrolysate of crab was concentrated in vacuum. Comparatively speaking, the vacuum concentration temperature had a greater impact on crab taste than the concentration volume. The results of GC-MS analysis showed that the relative mass concentration of volatile flavor substances in four groups of samples was RCEL>50CES>HPEC>50EW, and their values were 13.9753, 8.3862, 6.2235, and 1.0855 μg/L, respectively. It could be seen the obviously reduced flavor substances with sample of 50CES after vacuum concentration. GC-MS showed that the important flavor substances forming crab flavor might be aldehydes (benzaldehyde, anisaldehyde, 3-ethylbenzaldehyde and 2,4,5-trimethylbenzaldehyde), esters (n-benzoyl glycine methyl ester), ketones (butyrylacetone and benzylidene acetophenone), hydrocarbons (2,2-dimethyl tetradecane, undecane, 9-octyl icosane and n-nenenebd eicosane), ethers (an ether of 4-allylanisole）and heterocyclic class (2,5-dimethylpyrazine), etc.